Determining the Priority Element in Safety Management System of Public Transport with Analytic Hierarchy Process (AHP) - Rahmita, Destria; Purwanto, Edi; Pranoto, Ethys; Rusmandani, Pipit (RSF Conference Series: Engineering and Technology, 2022)
Safety Management of Public Transport Company (SMK-PAU) has become mandatory for all transportation service providers. SMK-PAU has ten elements of management systems. This present study aims to illustrate how the ten elements are employed. Analytic Hierarchy Process (AHP) was used to determine which of the ten elements is a priority in the Safety Management of Transportation Company in accordance with Transportation Ministerial Regulation No 85 of 2018 concerning the Safety Management of Public Transport Company based on the respondent group. The respondents were academics, regulators, and operators of public transport. The finding revealed that the precedence element was the element of hazard and risk management as well as the enhancement of competency and training.